👤
Bart80215
a fost răspuns

Ajutaţi vă rog frumos​

Ajutaţi Vă Rog Frumos class=

Răspuns :

Explicație pas cu pas:

[tex]\Big[0,4 + 0,(6)\Big] \cdot \Big(-1 \frac{1}{4}\Big) : 0,(3) = \Big( \frac{4}{10} + \frac{6}{9} \Big) \cdot \Big(-\frac{5}{4}\Big) : \frac{3}{9} = \\ [/tex]

[tex]= - \Big( \frac{2}{5} + \frac{2}{3} \Big) \cdot\frac{5}{4} : \frac{1}{3} = - \frac{6 + 10}{15} \cdot\frac{5}{4} \cdot 3 = - \frac{16}{15} \cdot\frac{5}{4} \cdot 3 \\ [/tex]

[tex]= - \frac{16}{15} \cdot\frac{5}{4} \cdot 3 = - \frac{4}{3} \cdot 3 = \bf - 4 \\ [/tex]

[tex]\it =\ \Big(\dfrac{\ 4^{(2}}{10}+\dfrac{\ 6^{(3}}{9}\Big)\cdot\Big(-\dfrac{5}{4}\Big):\dfrac{3}{9}=-\Big(\dfrac{^{3)}2}{\ \ 5}+\dfrac{^{5)}2}{\ \ 3}\Big)\cdot\dfrac{5}{4}\cdot3=-\dfrac{16}{\not15}\cdot\dfrac{\not15}{4}=-4[/tex]